Rethinking Female Sainthood: Michèle Roberts’ Spiritual Quest in Impossible Saints - Rodríguez, Patricia Bastida (Feminist theology, 2006)
Women’s marginalized position in Christianity has been a central concern in much of Michèle Roberts’ fiction, springing from her Catholic education and her awareness of the sexist ideology underlying Christian doctrine. Her growing fascination with the figure of the female saint is reflected in Impossible Saints,1 her most recent novel dealing with Christianity, where she offers an utterly transgressive exploration of female sainthood through the subverted, fictionalised lives of a number of women who have been canonized as saints by the Church. This paper examines the global message of Impossible Saints as a radical questioning of the traditional Christian perception of the female saint, as well as its role in Roberts’ spiritual development and in her search for an empowering image of woman in the religious sphere.